Cognitive Behaviour Therapy with Roy Adaptation Approach on Improving Adolescent Self-Esteem in the Special Institution for Children Class I Martapura - Sitanggang, Yohana Agustina; Lani, Tiara; Raziansyah, Raziansyah (STIKep PPNI Jawa Barat, 2024)
Aims: This research aims to examine the impact of cognitive behaviour therapy with Roy's adaptation approach on increasing adolescent self-esteem in the Special Development Institute for Children Class 1 Martapura. Methods: This research employed a Quasi-Experimental Pre-Post Test with Control Group design. The sample size consisted of 30 respondents, divided into 15 in the treatment group and 15 in the control group, selected using purposive sampling techniques. The research instrument utilized to measure self-esteem was the Rosenberg Self-Esteem Scale. Results: The outcomes revealed a significant increase in adolescent self-esteem before and after receiving cognitive behavior therapy with the Roy adaptation approach in the treatment group, with a p-value of 0.014 < 0.05. This indicates that there is a positive effect of administering cognitive behavior therapy with the Roy adaptation approach on adolescent self-esteem at the Class 1 Martapura Children's Special Development Institute. Conversely, the control group experienced a decline in self-esteem during the post-test measurement. Conclusion: Cognitive Behaviour Therapy with Roy's adaptation theory approach conducted in 3 sessions is able to improve the self-esteem of adolescents who are in the Class 1 Martapura Children's Special Development Institute.